PROFIL SOSIOEKONOMI KOMUNITI PENDUDUK KAWASAN SETINGGAN DI KAMPUNG RAILWAY, KUALA LUMPUR - Tan, Hui Theng (Universiti Malaysia Sarawak (UNIMAS), 2009)
In Malaysia, squats can be found in various locations such as roadside, hilly areas, and city outskirts. Kampong Railway is a long established squatter settlement in Kuala Lumpur. The formation of Kampong Railway began from the construction of railway tracks at the end year 1800. This paperwork discusses the social economic profile of Kampong Railway's community. The surroundings of the squats have been studied and 17 respondents have been interviewed to obtain data relating to the livelihood of the Kampong Railway residents in Kuala Lumpur. Qualitative and quantitative methods have been applied to analyze the acquired data. The findings demonstrate that residents of Kampong Railway carry strong sentimental values on their settlement therefore many refuse to leave the squats. Apart from that, this research has identified the reasons conceived by the residents as the factors that prevent developments in the area therefore preventing the abolishment of squatter settlements in Kuala Lumpur. This study includes the proposals of several policies that can be used to achieve zero squats. The government 's mission of zero squats is a big challenge and there are many efforts that still need to be accomplished in order to achieve this goal